Enhanced manganese ion removal from aqueous solution using graphene oxide nanocollector in ion flotation: mechanism, efficiency, and recyclability - Arash Sobouti; Bahram Rezai; Fatemeh Sadat Hoseinian (Scientific Reports)
Abstract The study presents a novel approach to wastewater treatment by utilizing graphene oxide (GO) as a nanocollector for the elimination of manganese (Mn) ions via the ion flotation. GO outperformed traditional collectors, achieving a maximum removal efficiency of 78.1% with optimized GO concentrations. The investigation into the number of GO layers and its Brunauer–Emmett–Teller (BET) surface area revealed that GO with 3–5 layers was most effective, attributed to its larger surface area and BET, which enhance the adsorption capacity. In optimal conditions with 3 to 5 layers of GO, 89.4% of Mn ions were removed. SEM, EDX, WDX, and FTIR confirmed the adsorption of Mn ions onto GO, providing evidence of the ion flotation process’s efficacy. GO was also very good at being reused; after three regeneration cycles, it kept more than 85% of its original adsorption capacity. This increased adsorption efficiency while lowering costs. The adsorption mechanism is explained by electrostatic attraction, surface complexation, and ion exchange, which facilitate the binding of Mn ions to the GO surface. This research offers new information about using GO as a nanocollector in ion flotation to eliminate other heavy metal ions for water treatment and addressing environmental problems.